Commissioning a clinical proton pencil beam scanning beamline for pre-clinical ultra-high dose rate irradiations on a cyclotron-based system - Saini, Jatinder; Erickson, Danielle P. Johnson; Vander Stappen, François; Ruth, Matt; Cui, Sunan; Gorman, Vanessa; Rossomme, Séverine; Cao, Ning; Ford, Eric C.; Meyer, Juergen; Bloch, Charles; Wong, Tony; et al. (Frontiers in Oncology, 2024)
BackgroundThis manuscript describes modifications to a pencil beam scanning (PBS) proton gantry that enables ultra-high dose rates (UHDR) irradiation, including treatment planning and validation.MethodsBeamline modifications consisted of opening the energy slits and setting the degrader to pass-through mode to maximize the dose rate. A range shifter was inserted upstream from the isocenter to enlarge the spot size and make it rotationally symmetric. We measured the beamline transport efficiency and investigated the variation in output due to the recombination of charge in the dose monitoring chamber. The output calibration was performed through a parallel plate chamber (PPC05), and an intercomparison was performed for various detectors. The pre-clinical field for mice irradiation consisted of different dose levels to deliver uniform doses in transmission mode. The field dose rates were determined through log files while scripting in TPS was used to estimate PBS dose rates. The survival experiments consisted of irradiating the full pelvis of the mice at UHDR and conventional dose rates.ResultsThe spot size was constant with beam current and had a sigma of 8.5 mm at the isocenter. The beam output increased by 35% at 720 nA compared to 5.6 nA, primarily due to recombination in the dose-monitoring ion chambers. The Faraday Cup and PPC05 agreed within 2%, while other detectors were within 3% of FC for dose rates <60 Gy/s. The pre-clinical fields’ PBS dose rate is above 45 Gy/sec for all voxels within the target volume. The average and PBS dose rates decrease as field size increases and approaches 40 Gy/s for a field size of 7x7 cm2. All UHDR arms showed better survival than the corresponding conventional dose rate arms.ConclusionsWe successfully modified a clinical system to perform UHDR pre-clinical experiments. As part of our pre-clinical experiments, we observed the FLASH effect concerning mice survival.